Antihyperglycemic and hypoglycemic activity of naturally occurring peptides and protein hydrolysates from easy-to-cook and hard-to-cook beans (Phaseolus vulgaris L.). (July 2019) - Valencia-Mejía, Erika; Batista, Karla A.; Fernández, Juan Jose A.; Fernandes, Kátia F.
Abstract: The present study was undertaken to examine the antidiabetic potential of naturally occurring peptides and hydrolysate fractions from easy-to-cook (ETC) and hard-to-cook (HTC) beans. All fractions were tested regarding their in vitro inhibitory activities against α-amylase and α-glucosidase as well as in vivo anti-hyperglycemic and hypoglycemic effects. Results evidenced that the peptide fractions with the lowest molecular weight (<3 kDa) have the highest inhibitory activities, and a 16.9%–89.1% inhibition of α-amylase and 34.4%–89.2% inhibition of α-glucosidase were observed. Regarding the antihyperglycemic activity, the fraction ETCNO3–10 showed a better performance than the positive control (acarbose). In addition, results from hypoglycemic activity evidenced that the tested peptide fractions were able to decrease the glucose levels at the same extension of glibenclamide, maintaining a constant basal glucose level without a postprandial hyperglycemia peak. Finally, it is possible to suggest that the naturally occurring peptides and hydrolysate fractions obtained from ETC and HTC common beans could be used in functional food production or pharmaceutical formulations to prevent diabetes. Graphical abstract: Unlabelled Image Highlights: Peptides from ETC and HTC beans inhibited the α-glucosidase activity. Naturally occurring peptides presented antihyperglycemic and hypoglycemic activities. Hydrolysate fractions were efficient in decrease the blood glucose levels.